Cultural Genealogy of Sufism in the Rejang Muslim Community: An Anthropological-Historical Study - Ismail Ismail; Mukhamad Hadi Musolin Subagio; Aziza Aryati; Ridho Syabibi; Sultan Gholand Astapala; Nafila Chaudittisreen (SCAD Independent, 2026)
The persistence of Sufism within local Muslim communities presents an important challenge to institutional-centered perspectives that often reduce Islamic spirituality to formal ṭarīqa structures and doctrinal practices. In the Indonesian context, limited attention has been paid to how Sufi values survive and reproduce themselves through culturally embedded mechanisms within indigenous societies. This study sought to explore the genealogy of Sufism within the Rejang Muslim community in Bengkulu and analyze how Sufi values are transmitted, localized, and maintained through cultural practices and communal life. It employed a qualitative descriptive–exploratory approach using interviews, participant observation, and document analysis involving religious leaders, traditional leaders, and community members in Rejang Lebong Regency. Data were analyzed thematically through a genealogical and cultural approach. The findings revealed that Sufism in the Rejang community operated not primarily through formal institutional structures, but through oral traditions, communal rituals, language, and everyday social interaction. Sufi values such as humility, patience, sincerity, and social harmony were continuously reproduced through culturally embedded practices that reinforce collective identity and communal cohesion. This study contributes to broader discussions on cultural Sufism, lived Islam, and the localization of religious traditions within indigenous Muslim societies.